Two new species of Camptopteroides (Camptopteroides) (Hymenoptera: Mymaridae) from the Oriental region with a key to Old World species - Sankararaman, Hariharakrishnan; Manickavasagam, Sagadai; Triapitsyn, Serguei V.; Huber, John T.; Kharbisnop, Bankerdonbor (Zootaxa, 2020)
An overview of the Oriental species of the nominate subgenus of Camptopteroides Viggiani (Hymenoptera: Mymaridae) is given. Two new species, C. (Camptopteroides) formosa Manickavasagam & Sankararaman sp. n. from India and C. (Camptopteroides) reducta Triapitsyn sp. n. from Thailand and Malaysia, are described, and C. formosa additionally compared to two unnamed species. The holotype male of the type species of this genus, C. armata Viggiani from Sri Lanka, is diagnosed and illustrated. A key to Old World species of Camptopteroides is provided.